Pre-colonial commercial networks in Southeast Asia (2014)
Southeast Asia is a region that currently constitutes an economic, political and cultural center of great importance in the world. To become one, it has gone through a series of different complex historical processes of long standing, one of which are the interregional commercial networks developed during the thirteenth and fifteenth centuries, before the arrival of representatives of European imperial powers and subsequent colonization. Its geopolitically strategic position, as part of the main trade network between China, Southeast Asia, India and the Middle East, caused this region to experience religious, cultural, political and commercial interaction, thanks to the maritime diasporas. Throughout history, Southeast Asia has become a dynamic space, characterized by a movement of people and objects; whose dynamism dates from a period prior to contact with Europeans. In that sense, the analysis of the exchange networks prior to such contact becomes pertinent, which in turn will allow us to understand the current regional context and identify the characteristics that forged its history and left its mark on the visible commercial relations even in the contemporary world.